The impact of CSR on nonprofit outcomes: how the choice of corporate partner influences reputation and supportive intentions. (17th August 2021) - Harrison, Virginia; Vafeiadis, Michail; Diddi, Pratiti; Conlin, Jeff
Abstract : Purpose: While research has shown that corporate social responsibility (CSR) can enhance a company's reputation, less is known about the effects of CSR communication on nonprofits. Hence, the current study seeks to understand how corporate reputation, message credibility and message source may impact consumers' attitudinal and behavioral intentions toward nonprofits. Design/methodology/approach: A 2 (corporate reputation: low vs high) × 2 (CSR communication source: newspaper blog vs nonprofit blog) between-subjects online experiment was conducted. Real-world corporations (Toyota and Volkswagen) and a nonprofit (World Wildlife Fund) were chosen based on a pretest. Findings: Nonprofit reputation increased after reading a CSR message, especially when it involved a partnership with a low-reputation corporation. Nevertheless, CSR partnerships with high-reputation corporations evoked higher volunteer intentions. Message credibility mediated the relationship between corporate reputation and nonprofit reputation. When the communication source was the nonprofit and the partnership involved a high-reputation corporation, positive evaluations of nonprofit likeability and competence resulted. Practical implications: Nonprofit communication managers should understand the merit of communicating CSR partnerships with their constituents, regardless of medium. Additionally, the choice of a corporate partner is important for certain nonprofit outcomes. Lastly, message credibility is another important factor that should be considered. Originality/value: The study bridges literature in communications that typically examines CSR by focusing on its effects on corporate outcomes with literature in nonprofit management that looks at nonprofit outcome measures. This study demonstrated that nonprofit–corporate alliances can also influence nonprofit reputation and donation/volunteer intentions based on the reputation of the corporate partner.